Researchers Offer Strategies to Build Community‐Driven Research in Nordic Region. Issue 27 (8th July 2014) - Lukes, Laura A.; Fleming‐Sharp, Laura; Fugmann, Gerlis
<x xml:space="preserve">Abstract</x> More effective incorporation of traditional knowledge into Arctic research, as well as better communication between northern residents and researchers, is crucial to understanding the Arctic and the changes it is experiencing. Furthermore, training opportunities for Arctic researchers in how to approach indigenous peoples, work with local experts, and incorporate traditional knowledge successfully and respectfully into research projects is essential.